2009
DOI: 10.1128/aac.00663-08
|View full text |Cite
|
Sign up to set email alerts
|

Intrapulmonary Pharmacokinetics and Pharmacodynamics of Posaconazole at Steady State in Healthy Subjects

Abstract: We evaluated the pharmacokinetics (PK) and pharmacodynamics (PD) of posaconazole (POS) in a prospective, open-label study. Twenty-five healthy adults received 14 doses of POS oral suspension (400 mg twice daily) with a high-fat meal over 8 days. Pulmonary epithelial lining fluid (ELF) and alveolar cell (AC) samples were obtained via bronchoalveolar lavage, and blood samples were collected during the 24 h after the last dose. POS concentrations were determined using liquid chromatography with tandem mass spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
57
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 22 publications
9
57
0
2
Order By: Relevance
“…), the ELF/plasma concentration ratio was 11 (142) (57) and lung transplant patients (143). It has been suggested that high intracellular posaconazole concentrations may explain its effectiveness for prophylaxis ( Fig.…”
Section: Lungmentioning
confidence: 99%
See 2 more Smart Citations
“…), the ELF/plasma concentration ratio was 11 (142) (57) and lung transplant patients (143). It has been suggested that high intracellular posaconazole concentrations may explain its effectiveness for prophylaxis ( Fig.…”
Section: Lungmentioning
confidence: 99%
“…For this reason, it may be more useful to present the tissue area under the concentrationtime curve (AUC) for comparison. There are few studies that do this for humans (56,57,58,59,60,61,62), and with one exception (59), all deal with pulmonary distribution. Most of the antifungal agents considered in this review do exhibit hysteresis.…”
Section: Limitations Of Current Understanding and Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the posaconazole-treated cells were found to resist infection by A. fumigatus 14,18 The protective effect of cell-associated posaconazole persisted for at least 48 h after removal of free drug. 18 Measurement of posaconazole kinetics in epithelial cells demonstrated that this prolonged post-antifungal effect was due to the persistence of high levels of drug within the epithelial cells, 18 thus providing an explanation for the prolonged post-antifungal effect reported in animal studies of posaconazole.…”
mentioning
confidence: 99%
“…Posaconazole has a large apparent volume of distribution (1,774 liters), suggesting extensive extravascular distribution and penetration into body tissues, and a long mean half-life of 35 h (9,15). Pharmacokinetic data exist for the distribution of posaconazole within plasma, epithelial lining fluid, and alveolar cells (3,6,(10)(11)(12), but there are no clinical data on the bioavailability of posaconazole for skin or its effectiveness against fungal pathogens that affect skin.…”
mentioning
confidence: 99%